Triaging of respiratory protective equipment on the assumed risk of SARS-CoV-2 aerosol exposure in patient-facing healthcare workers delivering secondary care: a rapid review. Issue 10 (16th October 2020) - Ramaraj, Prashanth; Super, Jonathan; Doyle, Ruben; Aylwin, Christopher; Hettiaratchy, Shehan
Abstract : Objectives: In patient-facing healthcare workers delivering secondary care, what is the evidence behind UK Government personal protective equipment (PPE) guidance on surgical masks versus respirators for SARS-CoV-2 protection? Design: Two independent reviewers performed a rapid review. Appraisal was performed using Critical Appraisal Skills Programme checklists and Grading of Recommendations, Assessment, Development and Evaluations methodology. Results were synthesised by comparison of findings and appraisals. Data sources: MEDLINE, Google Scholar, UK Government COVID-19 website and grey literature. Eligibility criteria: Studies published on any date containing primary data comparing surgical facemasks and respirators specific to SARS-CoV-2, and studies underpinning UK Government PPE guidance, were included. Results: Of 30 identified, only 3 laboratory studies of 14 different respirators and 12 surgical facemasks were found. In all three, respirators were significantly more effective than facemasks when comparing protection factors, reduction factors, filter penetrations, total inspiratory leakages at differing particle sizes, mean inspiratory flows and breathing rates. Tests included live viruses and inert particles on dummies and humans. In the six clinical studies (6502 participants) included the only statistically significant result found continuous use of respirators more effective in clinical respiratory illness compared with targeted use or surgical facemasks. There was no consistent definition of 'exposure' to determine the efficacy of respiratory protective equipment (RPE). It is difficult to define 'safe'. Conclusions: There is a paucity of evidence on the comparison of facemasks and respirators specific to SARS-CoV-2, and poor-quality evidence in other contexts. The use of surrogates results in extrapolation of non-SARS-CoV-2 specific data to guide UK Government PPE guidance. The appropriateness of this is unknown given the uncertainty over the transmission of SARS-CoV-2. This means that the evidence base for UK Government PPE guidelines is not based on SARS-CoV-2 and requires generalisation from low-quality evidence of other pathogens/particles. There is a paucity of high-quality evidence regarding the efficacy of RPE specific to SARS-CoV-2. UK Government PPE guidelines are underpinned by the assumption of droplet transmission of SARS-CoV-2. These factors suggest that the triaging of filtering face piece class 3 respirators might increase the risk of COVID-19 faced by some.